Reflections of the Participant Interns on “Training Workshop on Patient Counseling” - Piryani, Rano Mal; Piryani, Suneel; Sharma, Nitasha (Journal of BP Koirala Institute of Health Sciences, 2020)
Background: Reflections is one of the core professional skills and integral component of lifelong self-learning. In this study, the reflections of the participant interns on training workshop on “patient counseling” were assessed.Methods: This descriptive qualitative study assessed the reflections of the 74 participant interns of training workshops on “patient counselling”. The written reflections of the participant interns were taken with informed consent on “what is learnt from training workshop”; “personal thoughts or reactions about training workshop” and “how this training workshop helped you in care of patient”. The analysis for the qualitative data was done manually.Results: Sixty (81%) respondents stated that they learnt about methods and approaches of patients counselling. Fifty-five (74%) perceived that proper counselling strengthens communication and the doctor-patient relationship which leads to patients’ good compliance with the treatment, and improved care, and outcome. Seventy (94%) participants found the training workshop very useful and helpful in acquiring the counselling skills, learning communication skills and understanding doctor-patient relationship. Moreover, they felt that the training facilitated them in responding to COVID-19 related concerns of the patients.Conclusion: Patients counselling training is critical for interns to understand the importance of counselling in patients’ care. Reflections can help to consolidate the learning and identify the opportunities to improve patient care and address patient safety concerns.